The Effect Of Sustainable Investment On Company Value In The LQ45 Index In The Indonesian Capital Market - Suchi Fausia Tenda; Muhammad Yunus Kasim; Erwan Sastrawan; Fera Nayoan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Sustainable investment based on environmental, social, and governance (ESG) principles is increasingly influencing global capital markets. In Indonesia, research on ESG, especially for companies in the LQ45 index, is still limited. This study analyzes the impact of governance, environment, and social factors on company value for 29 companies that have been consistently listed in the LQ45 index from 2020 to 2024. Using panel data and purposive sampling, secondary data were collected from annual reports, sustainability reports, and IDX publications. Firm value was measured using Tobin's Q, while ESG was measured through governance (shareholder rights, board independence, transparency), environment (waste management, carbon emissions, energy), and social (CSR contributions, community relations). Data analysis used panel regression in E-Views 12 to process data from several companies over several time periods and to examine differences between companies and changes over time.